Problems and Challenges Faced by Women Entrepreneurs : A Study with Special Reference to Schedule Tribes and Schedule Caste Women Entrepreneurs in Yellagiri and Jawadhu Hills of Tamil Nadu - Anbalagan, K.; Saravanan, P. (AMC Indian Journal of Entrepreneurship, 2023)
The purpose of the study focused on the problems and challenges faced by women entrepreneurs in Yellagiri and Jawadhu Hills. Women empowerment is an ongoing process whereby women become able to acquire and organize themselves to increase their self-reliance, stress their independent right to make appropriate choices, and control resources, which has been assisting in challenges and eliminating their subordination. Entrepreneurship has become one of the most rational fields in management over the past three decades. In most developing countries, entrepreneurs are the real and most powerful heroes of economic life. The entrepreneurs in tribal areas like Yellagiri and Jawadhu Hills, in their latest intellect, are called self-starters and doers of businesses. Entrepreneurs are individuals who have established their own enterprise, firm, or business concern. In general, almost anyone who commences an industry, enterprise, or trading center is treated as an entrepreneur. We adopted a descriptive research design and used demographic information with well-structured research tools based on the following objectives: socio-economic conditions, knowledge of government schemes, and challenges faced by women entrepreneurs.